EDUKASI PENGELOLAAN SAMPAH SEBAGAI UPAYA PENINGKATAN PENGETAHUAN KADER POSYANDU DI RUSUN MARUNDA - Nisrinah, Nisrinah; Sitoayu, Laras; Dewanti, Lintang Purwara; Agustina, Noni; Siwi, Fathurrohmah Isnadia; Akbar, Yunata Kandhias (Jurnal AbdiMas Nusa Mandiri, 2026)
Household waste in Marunda remains an environmental problem because most of it has not been managed through sorting and utilization, thus potentially causing pollution and disease risks. This activity aims to evaluate the effect of household waste management education on the knowledge of eight Posyandu Toddler cadres as an empowerment effort in maintaining environmental health. The solution provided was interactive counseling on waste types, sorting, and the utilization of organic and inorganic waste. The level of knowledge was measured using questionnaires before and after the intervention, then analyzed using the Wilcoxon Signed-Rank Test. The level of knowledge was measured using questionnaires before and after the counseling, then analyzed using the Wilcoxon Signed-Rank Test to see changes in scores. The evaluation results showed a significance value of 0.084 (p > 0.05), which means there was no statistically significant difference in knowledge between before and after education. A longer duration of the activity and a larger sample size are needed to see a greater impact.